Palladium thin films for plasmonic hydrogen gas sensing - Maciak, Erwin (Photonics Letters of Poland, 2019)
In this study, I prepared BK7 glass slides coated by palladium (Pd) layer by PVD technique. These samples have been employed as plasmon active structures in classic Kretschmann-based SPR set-up. The application of H2 sensing structures based on palladium plasmonic active thin films have been tested and investigated. Hydrogen sensing properties of Pd films were investigated at room temperature The reflectances of p-polarized light from Pd thin films as a function of angle of incidence and wavelength were measured in synthetic air (or nitrogen) and in gas mixtures including hydrogen. Variations of the reflectance in the presence of hydrogen gas at room temperature revealed that the samples can sense hydrogen in a wide range of concentration (0–2% vol/vol) without saturation behavior. The dynamic properties with various concentration of H2 at low temperature and dry gas mixtures was investigated and the effects of these factors on the hydrogen sensing properties were analyzed. Full Text: PDF References G. Korotcenkov, Handbook of Gas Sensor Materials: Properties, Advantages, and Shortcomings for Applications (Springer, New York 2013). CrossRef W. Jakubik, M. Urbanczyk, E. Maciak, "SAW hydrogen gas sensor based on WO3 and Pd nanostructures", Procedia Chemistry 1 (1), 200 (2009). CrossRef W. Jakubik, M. Urbanczyk, E. Maciak, T. Pustelny, "Bilayer Structures of NiOx and Pd in Surface Acoustic Wave and Electrical Gas Sensor Systems", Acta Physica Polonica A 116(3), 315 (2009). CrossRef E. Maciak, Z. Opilski, "Pd/V2O5 fiber optic hydrogen gas sensor", J. Phys. France IV 129, 137 (2005). CrossRef E. Maciak,. "Fiber optic sensor for H2 gas detection in the presence of methane based on Pd/WO3 low-coherence interferometric structure", Proc. SPIE 10455, UNSP 104550W (2017). CrossRef X. Bevenot, A. Truillet, C. Veillas, H. Gagnaire, M. Clement, "Hydrogen leak detection using an optical fibre sensor for aerospace applications", Sens. Actuators B 67, 57 (2000). CrossRef J. Homola, S.S. Yee, G. Gauglitz, "Surface plasmon resonance sensors: review", Sensors and Actuators B 54, 3 (1999). CrossRef H. Raether, Surface plasmons on smooth and rough surfaces and on gratings (Springer-Verlag, Berlin-Heidelberg 1988). CrossRef P. Tobiska, O. Hugon, A. Trouillet, H.Gagnarie, "An integrated optic hydrogen sensor based on SPR on palladium", Sensors and Actuators, B 74, 168 (2001). CrossRef Z. Opilski, E. Maciak, "Optical hydrogen sensor employing the phenomenon of the surface plasmons resonance in the palladium layer", Proc. SPIE 5576, 202 (2004). CrossRef T. Pustelny, E. Maciak, Z. Opilski, A. Piotrowska, E. Papis, K. Golaszewska, "Investigation of the ZnO sensing structure on NH3 action by means of the surface plasmon resonance method", European Physical Journal-Special Topics 154, 165 (2008). CrossRef E. Maciak, M. Procek, K. Kępska, A. Stolarczyk, "Study of optical and electrical properties of thin films of the conducting comb-like graft copolymer of polymethylsiloxane with poly(3-hexyltiophene) and poly(ethylene) glycol side chains for low temperature NO2 sensing", Thin Solid Films 618, 277 (2016). CrossRef